Factors Affecting Employee Performance Mediated by Employee Motivation at PT. XYZ - Cika Rahmada; Chandra Wibowo Widhianto (Pusat Publikasi Nusantara, 2024)
This study aims to determine the Influence of Reward and Organizational Justice on Employee Performance Mediated by Employee Motivation (Empirical Study: Employees at PT. XYZ). The population taken in this study only focuses on all employees of PT. XYZ has 98 employees. The sampling technique in this study uses a saturated sampling technique, where all populations in this study are used as samples. This research method uses quantitative SEM analysis and uses PLS software. The results of the study show that Rewards have a positive and significant effect on employee performance. Organizational fairness has a positive and significant effect on employee performance. Rewards have a positive and significant effect on increasing employee motivation. Organizational fairness has a positive and significant effect on employee motivation. Employee motivation has a positive and significant effect on employee performance. Employee motivation can mediate the influence of rewards on employee performance. Employee motivation can mediate the influence of organizational justice on employee performance.